2020
DOI: 10.17113/ftb.58.02.20.6207
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase and Its Relationship with Ethylene During Ripening of Genetically Modified Tomato (Solanum lycopersicum)

Abstract: Research background. TomloxB is the main isoform of lipoxygenase associated with ripening and senescence of fruits. On the other hand, ethylene, a gaseous hormone, is essential for the regulation of ripening in climacteric fruits like tomatoes. However, the relationship between TomloxB and ethylene production has not been thoroughly studied. Therefore, we aim to assess the effect of exogenous ethylene in transgenic tomatoes that contain a silenced TomloxB gene, and subsequently evaluate lipoxygenase activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this experiment, a smaller weight loss of 8.5 % was obtained in GM fruits, with 3 mM at day 30. Here the synergistic effect is shown, between the afore mentioned mechanisms of action of OA and the silencing of TomLoxB gene, which decreased the production and expression of the same enzyme, preventing the fatty acids that constitute the membrane from being oxidized by the enzyme (Velázquez-López et al, 2020;León-García et al, 2017). This also contributed to maintaining lightness (L*) longer in GM-C (18 %) and GM-3mM (23 %) tomatoes at day 15 and GM-C (10 %) and GM-3mM (12 %) at day 30, compared to WT-C control fruits (36 L*, day 15; 34 L*, day 30).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…In this experiment, a smaller weight loss of 8.5 % was obtained in GM fruits, with 3 mM at day 30. Here the synergistic effect is shown, between the afore mentioned mechanisms of action of OA and the silencing of TomLoxB gene, which decreased the production and expression of the same enzyme, preventing the fatty acids that constitute the membrane from being oxidized by the enzyme (Velázquez-López et al, 2020;León-García et al, 2017). This also contributed to maintaining lightness (L*) longer in GM-C (18 %) and GM-3mM (23 %) tomatoes at day 15 and GM-C (10 %) and GM-3mM (12 %) at day 30, compared to WT-C control fruits (36 L*, day 15; 34 L*, day 30).…”
mentioning
confidence: 82%
“…Lipoxygenase (LOX) activity was assayed according to Velázquez-López et al (2020), using linoleic acid as substrate. Tomato juice was extracted and centrifuged for 5 min at 8765xg in an Eppendorf centrifuge model 5415R (Hamburg, Germany).…”
Section: Lipoxygenase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect that has been investigated in tomato is the correlation between ET action and membrane catabolic enzymes such as phospholipases ( Natalini et al., 2017 ) and lipoxygenase ( Velázquez-López et al., 2020 ). By silencing the main isoform of lipoxygenase encoding gene ( TomloxB ) it was possible to conclude that lipoxygenase could be a regulator of ET synthesis through the activity of the enzyme ACO.…”
Section: Ethylene-related Postharvest Management and Physiological Re...mentioning
confidence: 99%
“…By silencing the main isoform of lipoxygenase encoding gene ( TomloxB ) it was possible to conclude that lipoxygenase could be a regulator of ET synthesis through the activity of the enzyme ACO. The Authors suggested that this discover could be useful for improving the shelf-life extension and the postharvest management of tomato ( Velázquez-López et al., 2020 ).…”
Section: Ethylene-related Postharvest Management and Physiological Re...mentioning
confidence: 99%